Hollow glass microsphere modified filler masterbatch for shoe midsole and preparation method thereof

By using hollow glass microbead modified filler masterbatch in the midsole, the problem of fatigue deformation of the midsole material after long-term use is solved, and better stiffness, hardness and rebound performance are achieved, and wear comfort and service life are improved.

CN119775760APending Publication Date: 2025-04-08SHANXI HAINUO TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411996205.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing midsole materials for shoes are prone to fatigue deformation after long-term use, which affects the comfort of wearing and the skewed force when walking.

Method used

Filled masterbatches modified with hollow glass microbeads, including thermoplastic elastomers, hollow glass microbeads, expanded perlite powders, coupling agents, dispersants and antioxidants, are prepared by extrusion granulation mechanism to add to the midsole formula of lightweight foamed thermoplastic elastomer shoes.

Benefits of technology

The stiffness, hardness and rebound performance of the midsole of the shoe are effectively adjusted to prevent fatigue and deformation, improve wear comfort and stability during walking, while maintaining excellent rebound and toughness, extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224566760000121
    Figure BDA0005224566760000121
  • Figure BDA0005224566760000131
    Figure BDA0005224566760000131
Patent Text Reader

Abstract

The invention discloses a hollow glass microsphere modified filling masterbatch for shoe midsoles and a preparation method thereof, and relates to the technical field of shoe midsoles materials. The filling masterbatch is calculated by weight and includes the following components: 60-90 parts of thermoplastic elastomer, 10-30 parts of hollow glass microspheres, 8-15 parts of expanded perlite powder, 0.1-2 parts of coupling agent, 0.5-2 parts of dispersant, and 0.1-2 parts of antioxidant; the preparation method includes the following steps: mixing the above raw materials and extruding them through an extrusion granulator, and pelletizing the extruded material strips to obtain the required filling masterbatch. The filling masterbatch is applied to shoe midsoles and can be used for daily shoes such as travel shoes, sports shoes, casual shoes, and fashion shoes. While being lightweight, creep-resistant, and wear-resistant, the hardness and rebound performance of the shoe midsoles can be adjusted in a wide range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shoe midsole materials, in particular to a hollow glass microbead-modified filling masterbatch for shoe midsole and a preparation method thereof. Background Art

[0002] As the midsole of travel shoes, sports shoes, casual shoes, fashion shoes, etc., it is required to be light, crisp, environmentally friendly and odorless, and also requires excellent resistance to compression deformation, excellent elasticity and good soft touch.

[0003] The currently widely used lightweight foam midsole is a type of material that has both plastic and rubber properties and is heat-plastic. Currently, the commonly used materials include EVA (ethylene-vinyl acetate copolymer), TPU (thermoplastic polyurethane elastomer), TPEE (thermoplastic polyester elastomer), PEBA (polyether block amide) and TPR (thermoplastic rubber). However, the common problems are that the thermoplastic elastomer foam material is not rigid enough, has low mechanical strength, uneven pores, low surface smoothness, is easy to collapse under external force, is easy to creep under heat, has a strong odor, etc. The force line of consumers walking in shoes is more skewed, and they are easy to be "flattened" after wearing for a long time, and the foot feel will become hard, thereby reducing the rebound and shock-absorbing performance. At the same time, the resistance to temperature changes, wear resistance and durability are also poor, thus affecting the consumer's wearing experience. Under this premise, pursuing a better performance balance point between lighter, higher rebound and lower compression deformation, further improving the overall wearing experience, and satisfying consumers' pursuit of quality and comfort is a very worthy issue to think about.

[0004] After searching domestic patent documents in the past 15 years, the keyword "application of hollow glass microspheres in shoe materials" yielded an invention patent and a technical document, as follows:

[0005] Patent No. ZL201210302736.5 discloses "a kind of heat-insulating midsole shoe material", which specifically discloses that: the shoe material is mainly processed from the following raw materials: styrene emulsion, nano silicon dioxide, hollow glass microbeads and pearl powder. Processing method: firstly, nano silicon dioxide, hollow glass microbeads and pearl powder are mixed and added to a ball mill for ball milling, the mixed powder after ball milling is added to the styrene emulsion, stirred evenly, and then the mixed raw materials are added to the soaking tank; the non-woven fabric is passed through the soaking tank and repeatedly squeezed so that the mixed raw materials are fully immersed in the non-woven fabric, and then the non-woven fabric with the material is sent to a drying box for drying to form non-woven leather, and then aluminum foil is attached to the bottom surface of the dried non-woven leather to form the heat-insulating midsole shoe material. Compared with the prior art, the heat-insulating midsole shoe material of the present invention has the characteristics of simple processing technology, low production cost, good insulation effect, etc., and can effectively avoid the influence of the high temperature of the surface on the temperature inside the shoe, so as to achieve the purpose of protecting the sole of the foot.

[0006] The paper titled "Application of High-Performance Hollow Glass Microspheres in the Field of Shoe Materials" was written by Guo Jie. He discussed the advantages of using hollow glass microspheres (abbreviated as HGM) in shoe materials and explained the application cases of high-performance hollow glass microspheres in shoe materials. This is a micron-sized hollow glass microsphere with a smooth surface. The hollow structure is filled with rarefied gas, which has the characteristics of light weight and heat insulation. Adding hollow glass microspheres to shoe materials can significantly reduce the weight of the soles while hardly increasing production costs. In addition, the fluidity of hollow glass microspheres is good, which can further improve the fluidity of the rubber and show better mold filling during sole molding; rigidity is shrinkage-resistant and has a certain skeleton support effect. According to the public information so far, the application of hollow glass microspheres in the midsole of foamed shoes has not been found, nor has the application of hollow glass microsphere-modified midsole filling masterbatch in the midsole of foamed shoes been found. Summary of the invention

[0007] The invention provides a hollow glass microsphere modified filling masterbatch for a shoe midsole and a preparation method thereof, so as to solve the problem that the shoe midsole of the prior art may be fatigued and deformed over a long period of time.

[0008] The hollow glass microsphere modified filling masterbatch for shoe midsoles provided by the present invention comprises the following components, calculated by weight: 60-90 parts of thermoplastic elastomer, 10-30 parts of hollow glass microspheres, 8-15 parts of expanded perlite powder, 0.1-2 parts of coupling agent, 0.5-2 parts of dispersant and 0.1-2 parts of antioxidant.

[0009] Preferably, the thermoplastic elastomer is TPU, or TPE resin, or EVA; wherein the TPE resin is a mixture of SBS, SEBS, SEPS and cyclohexane oil, and the weight percentage of vinyl acetate in the EVA is 15% to 28%.

[0010] Preferably, the hollow glass microspheres have a particle size of 10 to 60 microns and a density of 0.44 to 0.60 g / cm 3 ; The size of the expanded perlite powder is 100 to 300 meshes.

[0011] Preferably, the coupling agent is a silane coupling agent, an aluminate coupling agent, a borate coupling agent or a phthalate coupling agent.

[0012] Preferably, the dispersant is polyethylene wax powder with a maleic anhydride grafting rate of 5% to 8%.

[0013] Preferably, the preparation method of the polyethylene wax powder with a maleic anhydride grafting rate of 5% to 8% is as follows, and the following parts are all parts by weight:

[0014] (A) Chemical modification: 100 parts of polyethylene wax powder were vacuum dried at 60° C. for more than 6 hours, then placed in a stainless steel reactor, and 300 parts of a benzene / ethyl acetate mixed solvent were added, with the weight ratio of benzene to ethyl acetate being 85:15. The mixture was heated while being stirred, and a reflux condenser was turned on. When the temperature of the reactor liquid reached 75-80° C., the temperature was maintained. After the polyethylene wax powder was fully dissolved, the oxygen-containing air in the reactor was replaced with nitrogen. Then, 8 parts of maleic anhydride and 0.5-1 part of a peroxide initiator were added, wherein the peroxide initiator was dry BIBP or BPO. The stirring blade speed was 100-200 rpm, and the reactor liquid temperature was maintained at 75-80° C. The reaction was timed for 8 hours;

[0015] (B) Solvent recovery: After the chemical modification reaction is completed, the reflux condenser is closed, the distillation condenser is opened, and then the stainless steel reactor is gradually heated and the distilled mixed solvent is cooled and recovered through the distillation condenser for the next chemical modification until the melt temperature in the reactor is above 160° C., and then the residual volatiles in the reactor are removed by vacuum;

[0016] (C) Finished powder: Then raise the temperature of the material in the reactor to 180-190°C, open the discharge valve, pour the molten material in the reactor into a stainless steel square plate, wait for it to cool, cut it into pieces, and then grind it into powder using a pulverizer.

[0017] Preferably, the antioxidant is a powdered phenolic antioxidant.

[0018] The present invention also relates to a method for preparing the above-mentioned hollow glass microsphere modified filling masterbatch for shoe midsoles, comprising the following steps: first, the hollow glass microspheres, the expanded perlite powder, the coupling agent, the dispersant, and the antioxidant are mixed and stirred evenly according to the formula ratio, and added to the side feeder hopper for standby; then the thermoplastic elastomer is put into the main feeder hopper of the extrusion granulator; the main feeder is started first to extrude the thermoplastic elastomer strips, and the strips are cooled and pelletized in a water tank, and after normal operation, the side feeder is started again and adjusted to the required feeding amount to obtain the required extruded strips filled with hollow glass microspheres and expanded perlite powder, and the extruded strips are pelletized to obtain the required filling masterbatch.

[0019] Preferably, the extrusion granulator is a twin-screw extrusion granulator with a mid-section side feeder, and the aspect ratio of the twin screw is (33-55):1.

[0020] Preferably, the operating temperature of the extrusion granulator is 110-150°C, the extrusion die temperature is 90-110°C, the entire barrel shall not have an exhaust device or the exhaust device is in a completely closed state, and the main engine screw speed is 200-300 rpm.

[0021] Preferably, the total weight percentage of the hollow glass microspheres and the expanded perlite powder in the extruded material strip filled with the hollow glass microspheres and the expanded perlite powder is 10% to 30%.

[0022] The beneficial effects of the present invention are:

[0023] The hollow glass microsphere modified filling masterbatch for shoe midsoles of the present invention and the preparation method thereof are used to adjust the stiffness, hardness, rebound and other properties of lightweight foamed shoe midsoles, and prevent the shoe midsoles from fatigue deformation for a long time, which affects the wearing comfort and the force deviation during walking. The hollow glass microsphere modified filling masterbatch is applied to travel shoes, sports shoes, casual shoes, fashion shoes, etc., and the filling masterbatch is added in a weight ratio of 15% to 25% to the lightweight foamed thermoplastic elastomer shoe midsole formula, and the obtained shoe midsole density is 0.6 to 0.9 g / cm 3 , lightweight and high strength, can improve the overall comfort, durability and functionality of the shoes, maintain excellent resilience and toughness, and is not prone to permanent deformation after long-term use, providing customers with an environmentally friendly, lightweight and more comfortable experience; at the same time, scraps can be recycled, saving resources and benefiting environmental protection. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The following embodiment of the present invention discloses a hollow glass microsphere modified filler masterbatch for shoe midsoles, which comprises the following components, calculated by weight: 60 to 90 parts of thermoplastic elastomer, 10 to 30 parts of hollow glass microspheres, 8 to 15 parts of expanded perlite powder, 0.1 to 2 parts of coupling agent, 0.5 to 2 parts of dispersant, and 0.1 to 2 parts of antioxidant.

[0026] The thermoplastic elastomer in the following embodiments is TPU, or TPE resin, or EVA; wherein, the TPE resin is a mixture of SBS (styrene-butadiene-styrene block copolymer), SEBS (a triblock copolymer consisting of polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenation of polybutadiene as the middle elastic block), SEPS (styrene-ethylene-propylene-styrene type block copolymer) and cycloalkane oil, and the weight percentage of VA (vinyl acetate) in EVA is 15% to 28%; these thermoplastic elastomers can be selected from common products on the market, such as TPU-T2175 of Shandong Yinuowei Polyurethane Co., Ltd., TPE-AK460 of Ningbo Aoke Polymer New Materials Co., Ltd., and EVA-V5110J of Yangzi Petrochemical-BASF Co., Ltd.

[0027] The hollow glass microspheres in the following embodiments can be selected from common products on the market, such as K46 of 3M Company in the United States, HN50 of Shanxi Hainuo Technology Co., Ltd., etc., whose main component is soda lime borosilicate glass, and whose structure is a micron-level glass-enclosed hollow sphere with nitrogen inside. The appearance is white powder, and the preferred particle size is 10 to 60 microns and the density is 0.44 to 0.60 g / cm 3 .

[0028] The expanded perlite powder in the following embodiments can be selected from common products on the market, such as 100-300 mesh expanded perlite powder produced by relevant enterprises in Xinyang City, Henan Province. Expanded perlite powder is a suspended ultrafine white powder formed above the receiving bin after the perlite ore is preheated, instantaneously calcined and expanded at high temperature.

[0029] The coupling agent in the following embodiments is a silane coupling agent, or an aluminate coupling agent, or a borate coupling agent or a phthalate coupling agent, preferably a powdered aluminate coupling agent or a borate coupling agent or a compound of the two at room temperature; the dispersant in the following embodiments is a polyethylene wax powder with a maleic anhydride grafting rate of 5% to 8%, preferably a polyethylene wax powder with a maleic anhydride grafting rate of 6% to 7%; the antioxidant in the following embodiments is a powdered phenolic antioxidant, preferably antioxidant B225. The above reagents can all be selected from common products on the market.

[0030] In the following embodiments, a self-made polyethylene wax powder with a maleic anhydride grafting rate of 5% to 8% can be used, and the specific preparation method is as follows (the following parts are all parts by weight):

[0031] (A) Chemical modification: 100 parts of polyethylene wax powder were vacuum dried at 60°C for more than 6 hours, then placed in a stainless steel reactor, and 300 parts of a benzene / ethyl acetate mixed solvent (the weight ratio of benzene to ethyl acetate was 85:15) were added, and the temperature was raised while stirring, and the reflux condenser was turned on at the same time. When the reactor liquid temperature reached 75-80°C, the temperature was maintained. After the polyethylene wax powder was fully dissolved, the oxygen-containing air in the reactor was replaced with nitrogen, and then 8 parts of maleic anhydride and 0.5-1 part of a peroxide initiator were added. The peroxide initiator was dry BIBP (methyl-di-tert-butylperoxyisopropylbenzene) or BPO (benzoyl peroxide). The stirring blade speed was 100-200 rpm, and the reactor liquid temperature was maintained at 75-80°C. The reaction was timed for 8 hours.

[0032] (B) Solvent recovery: After the chemical modification reaction is completed, the reflux condenser is closed and the distillation condenser is opened. The stainless steel reactor is then gradually heated and the distilled mixed solvent is cooled and recovered through the distillation condenser for the next chemical modification until the melt temperature in the reactor is above 160°C. The residual volatiles in the reactor are then removed by vacuum.

[0033] (C) Finished powder: Then raise the temperature of the material in the reactor to 180-190°C, open the discharge valve, pour the molten material in the reactor into a stainless steel square plate, wait for it to cool, cut it into pieces, and then grind it into powder using a pulverizer.

[0034] The following embodiment of the present invention also discloses a method for preparing the hollow glass microsphere modified filling masterbatch for shoe midsole, comprising the following steps:

[0035] Raw material preparation: 60-90 parts of thermoplastic elastomer, 10-30 parts of hollow glass microspheres, 8-15 parts of expanded perlite powder, 0.1-2 parts of coupling agent, 0.5-2 parts of dispersant, and 0.1-2 parts of antioxidant.

[0036] Production equipment: A twin-screw extruder granulator with a mid-section side feeder, the twin-screw aspect ratio is (33~55):1.

[0037] Preparation process: first, hollow glass microspheres, expanded perlite powder, coupling agent, dispersant and antioxidant are mixed and stirred evenly according to the formula ratio, and added to the side feeder hopper for standby; then the thermoplastic elastomer is put into the main feeder hopper of the extrusion granulator, the extrusion granulator is heated to 110-150°C, the extrusion die temperature is 90-110°C, the entire barrel shall not have an exhaust device or the exhaust device is completely closed, the main engine screw speed is 200-300 rpm, the main feeder is started first, the thermoplastic elastomer strip is extruded, and it is cooled and pelletized in a water tank. After it is normal, the side feeder is started again and adjusted to the required feeding amount, so that the total filling amount of the hollow glass microspheres and the expanded perlite powder in the extruded strip filled with hollow glass microspheres and expanded perlite powder accounts for 10% to 30% by weight, and the extruded strip is pelletized to obtain the required filling masterbatch.

[0038] Example 1

[0039] A method for preparing a hollow glass microsphere-modified filling masterbatch for a shoe midsole comprises the following steps:

[0040] Raw material preparation: by weight, 70 parts of TPU-T2175, 25 parts of K46 hollow glass microspheres, 8 parts of 100-mesh expanded perlite powder, 1.2 parts of aluminate coupling agent, 0.8 parts of homemade polyethylene wax powder dispersant with a maleic anhydride grafting rate of 6% to 7%, and 0.5 parts of B225 antioxidant.

[0041] Production equipment: A twin-screw extruder granulator with a mid-section side feeder, the twin screw length-diameter ratio is 40:1.

[0042] Preparation process: first, hollow glass microspheres, expanded perlite powder, coupling agent, dispersant and antioxidant are mixed and stirred evenly according to the formula ratio, and added to the hopper of the above-mentioned side feeder for standby; then TPU is put into the main feeder hopper of the extrusion granulator, the extrusion granulator is heated to 130-135°C, the extrusion die temperature is 90-100°C, the entire barrel shall not have an exhaust device or the exhaust device is completely closed, the main engine screw speed is 200-300 rpm, first start the main feeder, extrude TPU strips, and cool and pelletize them through a water tank. After normal, start the side feeder and adjust it to the required feeding amount to obtain the required extrusion strips filled with hollow glass microspheres and expanded perlite powder. According to the ash content test, the total filling amount of hollow glass microspheres and expanded perlite powder in the extrusion strips accounts for 30%±1% by weight. The extrusion strips are pelletized to obtain the required TPU+30%HGM filled masterbatch.

[0043] Example 2

[0044] A method for preparing a hollow glass microsphere-modified filling masterbatch for a shoe midsole comprises the following steps:

[0045] Raw material preparation: by weight, 75 parts of TPE-AK460, 25 parts of HN50 hollow glass microspheres, 10 parts of 200-mesh expanded perlite powder, 0.8 parts of aluminate coupling agent, 0.6 parts of homemade polyethylene wax powder dispersant with a maleic anhydride grafting rate of 6% to 7%, and 0.5 parts of B225 antioxidant.

[0046] Production equipment: A twin-screw extruder granulator with a mid-section side feeder, the twin screw length-diameter ratio is 35:1.

[0047] Preparation process: first, hollow glass microspheres, coupling agent, dispersant and antioxidant are mixed and stirred evenly according to the formula ratio, and added to the side feeder hopper for standby; then TPE is put into the main feeder feeding hopper of the extrusion granulator, the extrusion granulator is heated to 140-150°C, the extrusion die temperature is 100-110°C, the entire barrel shall not have an exhaust device or the exhaust device is completely closed, the main engine screw speed is 200-300 rpm, first start the main feeder, extrude TPE strips, and cool and pelletize them in a water tank. After normal, start the side feeder and adjust it to the required feeding amount to obtain the required extrusion strips filled with hollow glass microspheres and expanded perlite powder. According to the ash content test, the total weight of the hollow glass microspheres and expanded perlite powder in the extrusion strips accounts for 25%±1%. The extrusion strips are pelletized to obtain the required TPE+25%HGM filled masterbatch.

[0048] Example 3

[0049] A method for preparing a hollow glass microsphere-modified filling masterbatch for a shoe midsole comprises the following steps:

[0050] Raw material preparation: by weight, 78 parts of EVA-V5110J, 22 parts of HN50 hollow glass microspheres, 8 parts of 100-mesh expanded perlite powder, 1 part of aluminate coupling agent, 0.5 parts of homemade polyethylene wax powder dispersant with a maleic anhydride grafting rate of 6% to 7%, and 0.3 parts of B225 antioxidant.

[0051] Production equipment: A twin-screw extruder granulator with a mid-section side feeder, the twin screw length-diameter ratio is 45:1.

[0052] Preparation process: first, hollow glass microspheres, coupling agent, dispersant and antioxidant are mixed and stirred evenly according to the formula ratio, and added to the side feeder hopper for standby; then EVA is put into the main feeder feeding hopper of the extrusion granulator, the extrusion granulator is heated to 120-125°C, the extrusion die temperature is 90-100°C, the entire barrel shall not have an exhaust device or the exhaust device is completely closed, the main engine screw speed is 200-300 rpm, first start the main feeder, extrude EVA strips, and cool and pelletize them in a water tank. After normal, start the side feeder and adjust it to the required feeding amount to obtain the required extrusion strips filled with hollow glass microspheres and expanded perlite powder. According to the ash content test, the total weight of the hollow glass microspheres and expanded perlite powder in the extrusion strips accounts for 22%±1%. The extrusion strips are pelletized to obtain the required EVA+22%HGM filled masterbatch.

[0053] Example 4

[0054] A method for preparing a hollow glass microsphere-modified filling masterbatch for a shoe midsole comprises the following steps:

[0055] Raw material preparation: by weight, 60 parts of TPU-T2175, 10 parts of K46 hollow glass microspheres, 9 parts of 200-mesh expanded perlite powder, 0.1 parts of borate coupling agent, 1 part of homemade polyethylene wax powder dispersant with a maleic anhydride grafting rate of 5% to 6%, and 0.1 parts of B225 antioxidant.

[0056] Production equipment: A twin-screw extruder granulator with a mid-section side feeder, the twin screw length-diameter ratio is 33:1.

[0057] Preparation process: first, the hollow glass microspheres, coupling agent, dispersant and antioxidant are mixed and stirred evenly according to the formula ratio, and added to the side feeder hopper for standby; then the TPU is put into the main feeder feeding hopper of the extrusion granulator, the extrusion granulator is heated to 110-120°C, the extrusion die temperature is 100-110°C, the entire barrel shall not have an exhaust device or the exhaust device is completely closed, the main engine screw speed is 200-300 rpm, first start the main feeder, extrude the TPU material strip, and cool and pelletize it in a water tank. After it is normal, start the side feeder and adjust it to the required feeding amount to obtain the required extrusion material strip filled with hollow glass microspheres and expanded perlite powder. According to the ash content test, the total weight of the hollow glass microspheres and expanded perlite powder in the extrusion material strip accounts for 10%±1%, and the extrusion material strip is pelletized to obtain the required TPU+10%HGM filling masterbatch.

[0058] Example 5

[0059] A method for preparing a hollow glass microsphere-modified filling masterbatch for a shoe midsole comprises the following steps:

[0060] Raw material preparation: by weight, 90 parts of EVA-V5110J, 30 parts of HN50 hollow glass microspheres, 15 parts of 300-mesh expanded perlite powder, 2 parts of phthalate coupling agent, 2 parts of self-made polyethylene wax powder dispersant with a maleic anhydride grafting rate of 7% to 8%, and 2 parts of B225 antioxidant.

[0061] Production equipment: A twin-screw extruder granulator with a mid-section side feeder, the twin screw length-diameter ratio is 55:1.

[0062] Preparation process: first, hollow glass microspheres, coupling agent, dispersant and antioxidant are mixed and stirred evenly according to the formula ratio, and added to the side feeder hopper for standby; then EVA is put into the main feeder feeding hopper of the extrusion granulator, the extrusion granulator is heated to 120-130°C, the extrusion die temperature is 90-100°C, the entire barrel shall not have an exhaust device or the exhaust device is completely closed, the main engine screw speed is 200-300 rpm, first start the main feeder, extrude EVA strips, and cool and pelletize them through a water tank. After normal, start the side feeder and adjust it to the required feeding amount to obtain the required extrusion strips filled with hollow glass microspheres and expanded perlite powder. According to the ash content test, the total weight of the hollow glass microspheres and expanded perlite powder in the extrusion strips accounts for 15%±1%. The extrusion strips are pelletized to obtain the required EVA+15%HGM filled masterbatch.

[0063] Performance Testing

[0064] The filling masterbatch prepared in the above embodiment is specifically applied to the midsoles of shoes such as travel shoes, sports shoes, casual shoes, and fashion shoes. Samples are prepared and tested for performance comparison according to the following method:

[0065] (1) Compounding and granulation: any one or a mixture of EVA, TPU, TPEE, PEBA and TPR is selected, and the hollow glass microsphere-modified filler masterbatch and foaming aid in the above embodiment are added in a certain proportion, and granules are formed by a plastic extrusion granulator.

[0066] (2) Compression molding: Weigh a certain amount of granular material and place it into a flat mold (mold cavity thickness ≥ 20 mm). Shape it through a specified heating and foaming process. After cooling, take it out and cut it into 10 cm * 10 cm flat squares.

[0067] (3) Density test: Use a vernier caliper to measure the volume of the foam block, use an electronic balance to measure its weight, and calculate the density.

[0068] (4) Rebound test: Use a vertical elastic testing machine, with the thickness of the foam blocks ≥ 50 mm, to test the rebound height of a target dropped from a height of 1 meter onto the surface of the foam blocks.

[0069] (5) Hardness test: Use a Shore hardness tester (C) to test the average hardness of multiple locations on the surface of the foam block.

[0070] (6) Compression set: The test method is in accordance with GB / T 7759.1-2015 compression permanent set rate.

[0071] (7) Performance comparison: Under the condition of the final foam block density being similar, the proportion of the filler masterbatch prepared in the above embodiment is increased in the formula, and the data of rebound, hardness and compression deformation are compared to determine the approximate or approximate change curve and give a conclusion.

[0072] The foam blocks prepared with the above raw materials were compared and tested for performance, and the following conclusions were obtained:

[0073]

[0074]

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. Hollow glass microsphere modified filler masterbatch for shoe midsole, characterized by: Calculated by weight, it includes the following ingredients: 60-90 parts of thermoplastic elastomer, 10-30 parts of hollow glass microspheres, 8-15 parts of expanded perlite powder, 0.1-2 parts of coupling agent, 0.5-2 parts of dispersant, and 0.1-2 parts of antioxidant.

2. The hollow glass microsphere modified filler masterbatch for shoe midsoles according to claim 1, characterized in that: The thermoplastic elastomer is TPU, or TPE resin, or EVA; wherein the TPE resin is a mixture of SBS, SEBS, SEPS and naphthenic oil, and the weight percentage of vinyl acetate in the EVA is 15% to 28%.

3. The hollow glass microsphere modified filler masterbatch for shoe midsoles according to claim 1, characterized in that: The hollow glass microspheres have a particle size of 10 to 60 microns and a density of 0.44 to 0.60 g / cm 3 ; The size of the expanded perlite powder is 100 to 300 meshes.

4. The hollow glass microsphere modified filler masterbatch for shoe midsoles according to claim 1, characterized in that: The coupling agent is a silane coupling agent, an aluminate coupling agent, a borate coupling agent or a phthalate coupling agent.

5. The hollow glass microsphere modified filler masterbatch for shoe midsoles according to claim 1, characterized in that: The dispersant is polyethylene wax powder with a maleic anhydride grafting rate of 5% to 8%.

6. The hollow glass microsphere modified filler masterbatch for shoe midsoles according to claim 5, characterized in that: The preparation method of the polyethylene wax powder with a maleic anhydride grafting rate of 5% to 8% is as follows, and the following parts are all parts by weight: (A) Chemical modification: 100 parts of polyethylene wax powder were vacuum dried at 60° C. for more than 6 hours, then placed in a stainless steel reactor, and 300 parts of a benzene / ethyl acetate mixed solvent were added, with the weight ratio of benzene to ethyl acetate being 85:

15. The mixture was heated while being stirred, and a reflux condenser was turned on. When the temperature of the reactor liquid reached 75-80° C., the temperature was maintained. After the polyethylene wax powder was fully dissolved, the oxygen-containing air in the reactor was replaced with nitrogen. Then, 8 parts of maleic anhydride and 0.5-1 part of a peroxide initiator were added, wherein the peroxide initiator was dry BIBP or BPO. The stirring blade speed was 100-200 rpm, and the reactor liquid temperature was maintained at 75-80° C. The reaction was timed for 8 hours; (B) Solvent recovery: After the chemical modification reaction is completed, the reflux condenser is closed, the distillation condenser is opened, and then the stainless steel reactor is gradually heated and the distilled mixed solvent is cooled and recovered through the distillation condenser for the next chemical modification until the melt temperature in the reactor is above 160° C., and then the residual volatiles in the reactor are removed by vacuum; (C) Finished powder: Then raise the temperature of the material in the reactor to 180-190°C, open the discharge valve, pour the molten material in the reactor into a stainless steel square plate, wait for it to cool, cut it into pieces, and then grind it into powder using a pulverizer.

7. The hollow glass microsphere modified filler masterbatch for shoe midsoles according to claim 1, characterized in that: The antioxidant is a powdered phenolic antioxidant.

8. The method for preparing the hollow glass microsphere-modified filler masterbatch for shoe midsoles according to any one of claims 1 to 7, comprising the following steps: First, the hollow glass microspheres, the expanded perlite powder, the coupling agent, the dispersant, and the antioxidant are mixed and stirred evenly according to the formula ratio, and added into the side feeder hopper for standby; then the thermoplastic elastomer is put into the main feeder hopper of the extrusion granulator; the main feeder is started first to extrude the thermoplastic elastomer strips, and the strips are cooled and pelletized in a water tank, and after the strips are normal, the side feeder is started again and adjusted to the required feeding amount to obtain the required extruded strips filled with hollow glass microspheres and expanded perlite powder, and the extruded strips are pelletized to obtain the required filling masterbatch.

9. The method for preparing a hollow glass microsphere-modified filler masterbatch for shoe midsoles according to claim 8, wherein the extrusion granulator is a twin-screw extrusion granulator with a mid-section side feeder, and the aspect ratio of the twin screw is (33-55):

1.

10. The method for preparing a hollow glass microsphere-modified filler masterbatch for shoe midsoles according to claim 9, wherein the operating temperature of the extrusion granulator is 110-150° C., the extrusion die head temperature is 90-110° C., the entire barrel shall not have an exhaust device or the exhaust device is in a completely closed state, and the main engine screw speed is 200-300 rpm.

11. The method for preparing a hollow glass microsphere-modified filling masterbatch for shoe midsoles according to claim 8, wherein the total filling amount of the hollow glass microspheres and the expanded perlite powder in the extruded material strip filled with the hollow glass microspheres and the expanded perlite powder accounts for 10% to 30% by weight.

Citation Information

Patent Citations

  • Heat insulation midsole shoe material

    CN102813336A